2011
DOI: 10.1016/j.anbehav.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Social-learning abilities of wild vervet monkeys in a two-step task artificial fruit experiment

Abstract: Keywords artificial fruit Chlorocebus aethiops field experiment local enhancement manipulation task solving social learning tradition vervet monkey Social learning is the basis for the formation of traditions in both human and nonhuman animals. Field observations and experiments provide evidence for the existence of traditions in animals but they do not address the underlying social-learning mechanisms. We used an established laboratory experimental paradigm, the artificial fruit design, to test for copying of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Studies of multiple groups of wild primates within single populations have demonstrated social learning through field experiments (in four groups of lemurs, Schnoell & Fichtel, ; in up to 13 groups of marmosets, Gunhold, Massen, Schiel, Souto, & Bugnyar, ; Gunhold Whiten, & Bugnyar, ; in up to six groups of vervet monkeys, van de Waal et al, ; van de Waal et al, ; van de Waal, Borgeaud, et al, ; de Waal et al, ; de Waal, Claidière, & Whiten, ; van de Waal & Bshary, ). However, long‐term observations of these populations, with the aim of revealing potential intergroup differences, are to my knowledge lacking, until this present review of behavioural variation in wild vervet monkeys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of multiple groups of wild primates within single populations have demonstrated social learning through field experiments (in four groups of lemurs, Schnoell & Fichtel, ; in up to 13 groups of marmosets, Gunhold, Massen, Schiel, Souto, & Bugnyar, ; Gunhold Whiten, & Bugnyar, ; in up to six groups of vervet monkeys, van de Waal et al, ; van de Waal et al, ; van de Waal, Borgeaud, et al, ; de Waal et al, ; de Waal, Claidière, & Whiten, ; van de Waal & Bshary, ). However, long‐term observations of these populations, with the aim of revealing potential intergroup differences, are to my knowledge lacking, until this present review of behavioural variation in wild vervet monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted from July 2007 This site was chosen for the presence of a tourist road passing through the territories of six groups of vervet monkeys (Chlorocebus pygerythrus) allowing observers to travel easily from one group to another. The six groups were subject to social learning experiments during the course of this study (van de Waal & Bshary, 2011;van de Waal et al, 2010;van de Waal, Krützen, Hula, Goudet, & Bshary, 2012). All group compositions are detailed in Table 2.…”
Section: Study Areamentioning
confidence: 99%
“…In a two-step foraging task, vervet monkeys ( Cercocebus aethiops ) had to remove a rope blocking a door before opening that door to retrieve food. Although the trained model was ultimately successful at the task, other individuals failed to master it although they were exposed to a successful model, suggesting that the link between one gesture and the next in a several-steps task was not evident ( van de Waal and Bshary, 2011 ). Another example of a behavior, this time naturally occurring, that failed to spread is dental flossing in Japanese macaques ( Leca et al, 2010 ).…”
Section: Social Diffusion Experiments: Goals Methods and Outputsmentioning
confidence: 99%
“…Such evidence is often strongest in laboratory or other captive contexts where experimental controls are most tractable to arrange, most importantly the provision of opportunities to learn from a model performing a novel action, contrasted with a no‐model control condition, and/or to learn from either of two models displaying different behaviors. However, in the service of better understanding the implications of such social learning in the natural lives of animals, a small but growing number of experiments following these and other designs have now been engineered in the more challenging circumstances of the wild, providing evidence of social learning in a range of primates (Gunhold, Massen, Schiel, Souto, & Bugnyar, ; Gunhold, Whiten, & Bugnyar, ; Kendal et al, ; Schnoell & Fichtel, ; Schnoell, Dittmann, & Fichtel, ; van de Waal & Bshary, ; van de Waal, Borgeaud & Whiten, ; van de Waal, Renevey, Favre, & Bshary, ) and other mammalian and avian species (Aplin et al, ; Slagsvold & Wiebe, ; Thornton & Clutton‐Brock, ). Additionally, new statistical techniques like social network diffusion analyses have offered complementary and compelling evidence for social learning in wild birds (Aplin et al, ), primates (Hobaiter, Poisot, Zuberbühler, Hoppitt, & Gruber, ) and cetaceans (Allen, Weinrich, Hoppitt, & Rendell, ).…”
Section: Introductionmentioning
confidence: 99%